Clinical Improvement Following Operative Management of Ankle Fractures Among Patients With and Without Moderate to High Depressive Symptoms: An Analysis Using PROMIS. Issue 1 (January 2023) - Bernstein, David N.; Ramirez, Gabriel; Thirukumaran, Caroline P.; Samuel Flemister, A.; Oh, Irvin C.; Ketz, John P.; Baumhauer, Judith F.
Background: Understanding the recovery trajectory following operative management of ankle fractures can help surgeons guide patient expectations. Further, it is beneficial to consider the impact of mental health on the recovery trajectory. Our study aimed to address the paucity of literature focused on understanding the recovery trajectory following surgery for ankle fractures, including in patients with depressive symptoms. Methods: From February 2015 to March 2020, patients with isolated ankle fractures were asked to complete Patient-Reported Outcomes Measurement Information System (PROMIS) Physical Function (PF), Pain Interference (PI), and Depression questionnaires as part of routine care at presentation and follow-up time points. Linear mixed effects regression models were used to evaluate the patient recovery pattern, comparing the preoperative time point to <3 months, 3-6 months, and >6 months across all patients. Additional models that included the presence of depression symptoms as a covariate were then used. Results: A total of 153 patients met inclusion criteria. By 3-6 months, PROMIS PF (β: 9.95, 95% CI: 7.97-11.94, P  < .001), PI (β: −10.30, 95% CI: −11.87 to −8.72, P  < .001), and Depression (β: −5.60, 95% CI: −7.01 to −4.20, P  < .001) improved relative to the preoperative time point. This level of recovery was sustained thereafter. When incorporating depressive symptoms into our model as a covariate, the moderate to high depressive symptoms were associated with significantly and clinically important worse PROMIS PF (β: −4.00, 95% CI: −7.00 to −1.00, P  = .01) and PI (β: 3.16, 95% CI: −0.55 to 5.76, P  = .02) scores. Conclusion: Following ankle fracture surgery, all patients tend to clinically improve by 3-6 months postoperatively and then continue to appreciate this clinical improvement. Although patients with moderate to high depressive symptoms also clinically improve following the same trajectory, they tend to do so to a lesser level than those who have low depressive symptoms. Level of Evidence: Level III, case-control study.